PENERAPAN STRATEGI MENJAWAB SECARA BERGANTIAN BERPOLA LINGKARAN ROUND ROBIN UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA KELAS VI SDN 002 UKUI DUA KECAMATAN UKUI - Diyan Pertiwi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study is a class action that aims to improve learning outcomes in subjects PPKn sixth grade students of SDN 002 Ukui Dua. This research is motivated by the low activity and low teacher and student learning outcomes in subjects PPKn. The problem of this study is whether the implementation of a strategy to answer alternately patterned circle round robin can improve student learning outcomes in subjects PPKn in the sixth grade SDN 002 Ukui Dua? This PPKn was conducted over two cycles. Data collection techniques in this research using collection observation techniques, achievement test, and documentation. Techniques of analysis in this study is an analysis of the activities of teachers and students and learning outcomes in subjects PPKn sixth grade students SDN 02 Ukui Dua Kecamatant Ukui. The result showed that the activity of teachers has increased. At the first meeting of the first cycle of 41% was obtained with Simply Perfect category and the second meeting reached 55% with the category Fairly Perfect. In the second cycle 3 meeting to reach 75% by the Perfect category and the 4th meeting of the second cycle reaches 85% with the Perfect category. While the activity of students has increased. At the first meeting of the first cycle reaches 51% with the category Fairly Perfect and the second meeting with the percentage of 66% to the category Perfect. After the second cycle of the third meeting with a percentage of 75% with the Perfect category while in attendance for-4 with the percentage of 94% to the category of Most Perfect. Learning outcomes of students also increased from the previous students who achieve KKM only 8 votes with a percentage (45%) after the first cycle an increase in students worth over KKM which reached 14 people with a percentage of 70%. Cycle II students who achieve KKM 17 (85%).